2012
DOI: 10.5897/ajbm11.1924
|View full text |Cite
|
Sign up to set email alerts
|

Employment issues among Malaysian information and communication technology (ICT) graduates: A case study

Abstract: In the 21 st century, there has been a growing concern about the role of higher education institution and how well they are satisfying the employers' needs. Malaysian Prime Minister mentioned that only 23% of the workforce was highly skilled in year 2010. This percentage is much lower, compared with other developed countries. It was stressed that, there is a need to improve the composition of highly skilled workers to at least 37% by 2015, to become a developed nation. The purpose of this paper is to highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Research indicated that current graduates lack crucial skills needed by the industry such as creative and critical thinking skills, communication skills and problem-solving skills (Tan et. al, 2009;Ramakrishnan & Yasin, 2012). As Sharma et.…”
Section: Research Issuesmentioning
confidence: 99%
“…Research indicated that current graduates lack crucial skills needed by the industry such as creative and critical thinking skills, communication skills and problem-solving skills (Tan et. al, 2009;Ramakrishnan & Yasin, 2012). As Sharma et.…”
Section: Research Issuesmentioning
confidence: 99%